Atenção pré-natal em região de fronteira na vigência da pandemia da Covid-19 - Schapko , Taís Regina (2022)
Prenatal care includes prevention, promotion, diagnosis and treatment measures and is considered the most important strategy for health promotion in pregnancy. In Brazil, due to the COVID-19 pandemic, it was necessary to reorganize health services to meet the high demand for suspected and confirmed cases of the disease, which may have exacerbated existing gaps in prenatal care. The objective of the study was to understand prenatal care in a border region during the COVID-19 pandemic. This is a qualitative study of 27 participants, including women and health professionals, in primary care settings between August 2021 and January 2022 using semistructured, remote, and in-person interviews, with data analyzed using thematic analysis. Four thematic categories were identified: delayed initiation of prenatal care, partiality in prenatal health interventions, misleading health information in a pandemic period, and COVID-19 prevention interventions in pregnancy. Pregnancy during the pandemic was found to cause surprise, concern, and anxiety, which contributed to the postponement of prenatal care. Consultations were suspended at the beginning of the pandemic, and when they resumed, they took place in person, with little use of telecare and active seeking limited to residents of Brazil. Health services took measures to prevent infection through COVID-19. These measures included limiting escorts during visits. The COVID-19 pandemic has led to setbacks in prenatal care, such as the restriction of doulas or spouses during consultations and examinations, the exposure of groups of pregnant women with losses in health education, the postponement of the start of prenatal care and/or the impairment of its delivery, especially among Brazilian women residing in Paraguay. Telecare as a strategy for prenatal follow-up was introduced only hesitantly. Health services reorganized to maintain measures to prevent infection in an attempt to provide prenatal care in person. Health policies that integrate actions between border countries are needed to ensure prenatal care and/or its continuity through government programs and policies that take into account the specificities of this context.